O arrastão vai à praia: gentes, redes e visibilidades no balneário carioca - Ana Brasil Machado; Mariana de Oliveira Santos (Confins)
In the early 1990s, arrastões became known in Rio de Janeiro as events in which robberies were committed by youth gangs, particularly on the beaches.They shaped strongly the experience in these spaces and changing the imaginary about seaside practices in the city of Rio de Janeiro. This paper proposes to understand, from the analysis of newspaper news, the public debate that preceded the stabilization of the contents related to the arrastão and its location on the seashore beaches of the Southern Zone of Rio. This article proposes to understand, from the analysis of newspaper news, the public debate that preceded the stabilization of the content related to the trawler and its location on the seashore beaches of the Southern Zone of Rio. Back in the early 1980s, when arrastões took place in other areas of the city, the study continued until the "summer of the arrastão" (1991-1992), when the practice was definitively associated with the carioca seafront and was highly requalified. In addition to the definitions of the practice and the actors involved, the paper also seeks to highlight the elements that constituted the spatiality of such phenomenon, with emphasis on the centrality and visibility of public spaces, and the relationships and connections between different spaces in the city.